2012
DOI: 10.1021/ac203336u
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Glycan Profiles from IgG-Depleted Human Immunoglobulins Facilitated by Microscale Affinity Chromatography

Abstract: Among the most important proteins involved in the disease and healing processes are the immunoglobulins (Igs). Although many of the Igs have been studied through proteomics, aside from IgG, immunoglobulin carbohydrates have not been extensively characterized in different states of health. It seems valuable to develop techniques that permit us to understand changes in the structures and abundances of Ig glycans in the context of disease onset and progression. We have devised a strategy for characterization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
0
17
0
1
Order By: Relevance
“…Based on our previous studies, 10, 49 three remaining glycans have all been tentatively associated with the various immunoglobulins. In our previous cancer glycomic studies, we, along with others, have observed a general trend of decreased abundances of galactosylated glycans and elevated levels of those carbohydrates lacking this particular monosaccharide.…”
Section: Resultsmentioning
confidence: 89%
“…Based on our previous studies, 10, 49 three remaining glycans have all been tentatively associated with the various immunoglobulins. In our previous cancer glycomic studies, we, along with others, have observed a general trend of decreased abundances of galactosylated glycans and elevated levels of those carbohydrates lacking this particular monosaccharide.…”
Section: Resultsmentioning
confidence: 89%
“…23 In a similar fashion, immunoglobulins and their associated glycans can be probed in different states of health after their sequential purification through immobilized Protein G and Protein L microscale affinity columns. 36 …”
Section: Sample Preparation Fractionation and Preconcentrationmentioning
confidence: 99%
“…Třetí přístup vhodný pro účely glykoproteomiky je použití komerčně vyráběných mikrokolon Nukleosil 4000-7 (Macherey-Nagel GmbH & Co., Germany), které fungují na principu aniontového výmě-níku pro separaci proteinů a peptidů. Vhodnost mikrokolon je dána přede-vším chemickou inertností vůči zkoumanému vzorku (nedochází k nespecifi cké adsorpci jiných proteinů), kompaktností při užití HPLC (high performance liquid chromatography) a v neposlední řadě i velkým poměrem povrchu k objemu i pevností SiO 2 [49].…”
Section: Závěrunclassified